Wound dressings: Current advances and future directions - Rezvani Ghomi, Erfan; Khalili, Shahla; Nouri Khorasani, Saied; Esmaeely Neisiany, Rasoul; Ramakrishna, Seeram (Journal of applied polymer science, 2019)
ABSTRACT Wound healing is a complicated and continuous process affected by several factors, which needs an appropriate surrounding to achieve accelerated healing. Wound healing process recruits three different phases: inflammation, proliferation, and maturation. Due to the different types of wounds, as well as the advancement in medical technology, various products have been developed to repair different skin lesions. Our objective is to investigate the advancement in wound dressings from traditional to the current methods of treatment. The article presents the characteristics of an ideal wound dressing, the requirements for the appropriate selection of different types of wounds, and a detailed classification of wound dressings. Animal origin, herbal origin, and synthetic dressings are firstly introduced and reviewed. Then, nonmedicated dressings including alginate, hydrogel, and hydrocolloid dressings, as well as medicated dressings are discussed. Finally, the developmental prospectives of the new generations of wound dressings for future researches are presented. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47738.